Protein Conversion Factor and Antioxidant Capacity of Isoflavones in Glycine Max; [Factor de Conversión Proteica y Capacidad Antioxidante de Isoflavonas en Glycine Max] - Martinez-Salinas, J; Rios-Ramirez, M (MS-Editions, 2023)
The conversion factor of nitrogen to proteins and isoflavones present in Glycine max was determined. For the determination of the conversion factor, we worked with solubilizing the proteins at alkaline pH and then extracting them with acidic pH. The proteins were identified by the Kjeldahl method. The antioxidant capacity was determined after extracting the isoflavones and their glycosides through the Soxhlet method, and then using the Brand Williams method (DPPH). The results indicate that the protein conversion factor was 5.85, the maximum concentration of total isoflavones was 33.33%, the antiradical efficiency of total isoflavones was 0.004 mL/ug min, the antiradical efficiency of gallic acid was 0.005 mL/ug min. and the antiradical efficiency of tannic acid was 0.0004 mL/ug min. These results justify the consumption of Glycine max (Soya) as a food that has a high nutritional quality and provides an excellent source of antioxidants, which will prevent hormonal and carcinogenic diseases. © 2023, MS-Editions. All rights reserved.